Metabolic risk and television time in adolescent females - Machado-Rodrigues, Aristides M.; Leite, Neiva; Coelho-e-Silva, Manuel J.; Enes, Fernando; Fernandes, Rômulo Araújo [UNESP]; Mascarenhas, Luis P. G.; Boguszewski, Margaret C. S.; Malina, Robert M. (Springer, 2015)
Objectives A sedentary lifestyle is increasingly implicated in a negative metabolic health profile among youth. The present study examined relationships between clustered metabolic risk factors and TV viewing in female adolescents.Methods The sample comprised 262 girls 14-17 years. Height, weight, fasting glucose, insulin, HDL cholesterol, triglycerides, and blood pressure were measured. Body mass index (BMI) was calculated. TV viewing time and moderate-to-vigorous physical activity (MVPA) were estimated from a 3-day diary. Outcome variables were normalized and expressed as Z scores which were summed into a metabolic risk score. Multiple linear regression analysis was used.Results TV viewing was independently associated with increased prevalence of clustered metabolic risk in girls after adjustment for several confounders (i.e., chronological age, BMI, MVPA, and parental education). The final model also indicated that lower levels of MVPA, higher BMI, and lower mother education were associated with higher metabolic risk.Conclusions Increased TV viewing had an adverse effect on metabolic health of adolescent girls. The findings highlight the potential importance of preventive actions to ameliorate metabolic risk in youth which target both sedentary and physically active behaviors.
Keywords: Public health; Sedentary behavior; Youth; Overweight; Lifestyle